2015
DOI: 10.3892/ol.2015.3376
|View full text |Cite
|
Sign up to set email alerts
|

Forkhead box J1 expression is upregulated and correlated with prognosis in patients with clear cell renal cell carcinoma

Abstract: Abstract. The forkhead box (FOX) family of transcription factors are considered to have a role in tumorigenesis. FOXJ1 is a member of the FOX family; however, its function in human renal cell carcinoma (RCC) has remained to be elucidated. Therefore, the present study evaluated the expression of FOXJ1 in human clear cell RCC and the effect of FOXJ1 on the proliferative ability of RCC cells. The RCC specimens analyzed in the present study were obtained from 286 patients with RCC who underwent nephrectomy. FOXJ1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 43 publications
3
9
0
Order By: Relevance
“…EPHA10 was associated with a 1.4-fold change in our cohorts' relapsed samples, which supports data in breast cancer where its expression was associated with more aggressive disease [21]. Similarly, VAV3, KLK5 and FOXJ1 [22][23][24] were upregulated in relapsed samples, but the functional significance in clinical stage I TGCT is yet to be elucidated. In contrast to the studies by Korkola et al [18,19], immune pathways associated with B-cell and T-cell complement activation were not identified as key discriminating factors that separated relapsed from non-relapsed disease in the present cohort.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…EPHA10 was associated with a 1.4-fold change in our cohorts' relapsed samples, which supports data in breast cancer where its expression was associated with more aggressive disease [21]. Similarly, VAV3, KLK5 and FOXJ1 [22][23][24] were upregulated in relapsed samples, but the functional significance in clinical stage I TGCT is yet to be elucidated. In contrast to the studies by Korkola et al [18,19], immune pathways associated with B-cell and T-cell complement activation were not identified as key discriminating factors that separated relapsed from non-relapsed disease in the present cohort.…”
Section: Discussionsupporting
confidence: 86%
“…EPHA10 was associated with a 1.4‐fold change in our cohorts’ relapsed samples, which supports data in breast cancer where its expression was associated with more aggressive disease . Similarly, VAV3 , KLK5 and FOXJ1 were upregulated in relapsed samples, but the functional significance in clinical stage I TGCT is yet to be elucidated. In contrast to the studies by Korkola et al.…”
Section: Discussionsupporting
confidence: 85%
“…FOX transcription factor family, which is named after the forkhead winged-helix DNA-binding domain, 23 has been reported to act as important regulators of numerous biological processes, including cell cycle regulation, proliferation, differentiation, senescence, survival, metabolism and apoptosis. 24,25 A series of FOX genes, such as FOXC2, 26,27 FOXJ1, 28 FOXL1, 29 FOXM1, [30][31][32][33][34][35] and FOXPs, [36][37][38] have been reported to play vital roles in the carcinogenesis, metastasis and prognosis of ccRCC. A previous study reported that FOXK2 expression was elevated in human colorectal cancer and is associated with intestinal tumorigenesis; 20 two other studies reported that FOXK2 was downregulated in breast cancer and suppressed the carcinogenesis of breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Although none of the 12 SNPs in the high LD region were reported to function as an eQTL, changes in the FOX binding sites could potentially explain the involvement of the SNPs in the neuropathy because previous studies have shown a role of the FOXA genes in regulating the maintenance of dopaminergic function of neurons, particularly in the embryonic stages [ 33 ]. Additionally, FOXJ1 is a significant transcription factor in the central nervous and reproductive systems and overexpression of FOXJ1 has been reported to be highly associated with colon cancer stage and its outcome [ 34 , 35 ]. Motif changes for the FOX transcription factor family genes were observed also in other replicated loci in our study within 3p21.1 (rs4687753) and 5q23.2 (rs6891783) [ 36 ].…”
Section: Discussionmentioning
confidence: 99%